Characterization of Effluent Organic Matter (EfOM) in Domestic Wastewater Using Oxidation Ditch Algae Reactor (ODAR) with Microalgae Spirulina platensis - Imaniar Ramadhani; Mochammad Shaifullah Indrawanto; Euis Nurul Hidayah; Okik Hendriyanto Cahyonugroho (Nusantara Science and Technology Proceedings)
Oxidation ditch (OD) is a tub used to treat wastewater by utilizing oxygen and microorganisms contained in it to determine its ability to reduce the release of organic substances. Oxidation Ditch Algae Reactor (ODAR) is a biological wastewater treatment that utilizes the symbiosis between algae and bacteria in water. The results of biological processes contain organic material called effluent organic matter (EfOM). This research aims to investigate the characterization of effluent organic matter (EfOM) produced from the Oxidation ditch (OD) process with and without algae both in continuous aeration (oxic) and intermittent aeration (oxic-anoxic) conditions in domestic household wastewater and microalgae Spirulina platensis. Characterizing effluent organic matter (EfOM) is a crucial thing to understand its ability to treat wastewater. Based on the analysis results, the characterization of effluent organic matter (EfOM) in the oxidation ditch process using an algae ratio of 1:1 in continuous aeration (oxic) conditions through the UV254 test was identified as containing the highest aromatic organic matter up to 59.68%. Meanwhile, without using algae with a 1:0 ratio of intermittent aeration (oxic-anoxic) conditions, the lowest decrease in aromatic organic matter content reached 34.79%.